The Legal Status of Buying And Selling Wet Rice With Dry Rice: A Perspective of Fiqh Muamalah - Agnes Fitri Aryanti; Uswatun Hasanah (STAI Al-Mas'udiyah, 2026)
This study aims to analyze the practice and legal status of buying and selling wet rice with dry rice in Rejo Agung Village, Tegineneng District, Pesawaran Regency from the perspective of fiqh muamalah. The research problem departs from the community's habit of bartering wet rice with dry rice which has the potential to cause unclear dosage due to differences in water content and indications of riba fadhl and gharar. This study uses a qualitative approach with the type of field research. Data was obtained through observation, interviews with farmers who conducted transactions, and documentation, then analyzed descriptive-analytically through data reduction, data presentation, and conclusion drawn. The results of the study show that the practice of exchanging is carried out on the basis of people's habits and economic needs, but often does not take into account the equality of the dosage after the drying process, so that it has the potential to cause an imbalance in value. In the perspective of muamalah fiqh, rice is a usury item so that the exchange must meet the principles of equality (tamatsul), cash (taqabudh), and freedom from gharar. Therefore, this practice is invalid according to Islamic law because it contains elements of riba fadhl and resembles the practice of muzabanah.